A constitutionalist approach to the European Convention on Human Rights : the legitimacy of evolutive and static interpretation - Sonnleitner, Lisa (London [England] : Hart Publishing, 2022)
"This book presents a new constitutional argument for the legitimacy of evolutive interpretation of the ECHR. It constructs a model, in which evolutive and static constitutional principles are balanced with each other. The author argues that there are three possible interpretive approaches in time-sensitive interpretations of the ECHR, but that only one of them is justifiable by reference to the constitutional principles of the ECHR in every single case. The ECHR's constitutional principles either require an evolutive or static interpretation or they do not establish a preference relation at all, which leads to a margin of appreciation of the member states in the interpretation of the Convention. The balancing model requires the determination of the weights of the competing evolutive and static constitutional principles. For this purpose, the author defines weighting factors for determining the importance of evolutive or static interpretation in a concrete case."--
Introduction Part I: Fundamentals -- 1. On the Concepts of Law and Human Rights -- 2. A New Concept of Evolutive and Static Interpretation -- 3. The Legitimacy of Evolutive Interpretation Revisited -- 4. The Criticism Against Evolutive Interpretation Revisited Part II: The ECHR Constitution -- 5. The Argument of Constitutionalism -- 6. The Constitutional Nature of the ECHR -- 7. Three Basic Constitutional Principles of the ECHR Part III: Balanced Legitimacy Model -- 8. Setting the Scene for Balancing at the Interpretation Stage -- 9. The Balancing Model for Evolutive and Static Interpretation -- 10. External Justification Part IV: The Balanced Legitimacy Model Applied -- 11. The Right to Divorce -- 12. The Right to Assisted Suicide -- 13. The Right to Preservation of the Environment Conclusion -- Bibliography -- Index
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Convention for the Protection of Human Rights and Fundamental Freedoms; Human rights -- Europe; Electronic books